Effective Reduction in Opioid Prescriptions for Ambulatory Lesion Excisions in Pediatric Patients. Issue 3 (March 2021) - McKenna, Rachel A.; Lee, Alfred; Yan, Chen; Vu, Giap H.; Jantzen, Ellen C.; Brennan, Patrick J.; Watson, Adam; Burlingame, Caroline; Lin, Ines C.
Abstract : Background: Childhood opioid consumption is potentially deleterious to cognitive development and may predispose children to later addiction. Opioids are frequently prescribed for outpatient surgery but may not be necessary for adequate pain control. We aimed to reduce opioid prescriptions for outpatient pediatric skin and soft tissue lesion excisions using quality improvement (QI) methods. Methods: A multidisciplinary team identified drivers for opioid prescriptions. Interventions were provider education, improving computer order set defaults, and promoting non-narcotic pain control strategies and patient-family education. Outcomes included percentage of patients receiving opioid prescriptions and patient-satisfaction scores. Data were retrospectively collected for 3 years before the QI project and prospectively tracked over the 8-month QI period and the following 18 months. Results: The percentage of patients receiving an opioid prescription after outpatient skin or soft tissue excision dropped significantly from 18% before intervention to 6% at the end of the intervention period. Patient-reported satisfaction with pain control improved following the QI intervention. Satisfaction with postoperative pain control was independent of closure size or receipt of a postoperative opioid prescription. Intraoperative use of lidocaine or bupivacaine significantly decreased the incidence of postoperative opioid prescription in both bivariate and multivariate analyses. Results were maintained at 18 months after the conclusion of the QI project. Conclusion: Raising provider awareness, educating patients on expected postoperative pain management options, and prioritizing non-narcotic medications postoperatively successfully reduced opioid prescription rates in children undergoing skin and soft tissue lesion excisions and simultaneously improved patient-satisfaction scores.